Engineered Wood Products (EWP) and the perceptions of Malaysia’s architectural practitioner towards the application of EWP in buildings / Ong Beng Joo, Mohd Najib Mohd Salleh and Mazran Ismail - Beng Joo, Ong; Mohd Salleh, Mohd Najib; Ismail, Mazran (2022)
Construction activities cause the running out of natural resources and adverse environmental pollution. By substituting EWPs for traditional building materials such as concrete or steel, the total fossil fuel footprint of building construction can be greatly reduced. Despite being one of sustainable materials, the building construction industry has been reluctant to adopt engineered wood products for a number of reasons, including poor and inconsistent quality, connections with low social standing and fire performance, and costly and unpredictable material prices. This paper will study different types of (EWP) and the Malaysia architectural practitioner perception towards the application of engineered wood products as a building material. One hundred sets of questionnaires have been distributed to a targeted group of architectural practitioners namely architect, graduate architect, building draughtsman, inspector of work and building technologist in Malaysia that accounted for 52 respondents respectively. The data was analysed using Microsoft Excel through basic statistical analysis. It was found local architects have positive perception about the application of EWPs for building in Malaysia as shown by the survey findings. In contrary, it was found that most of the inspector of work do not have much knowledge about the application of EWP in building. It is suggested that the EWP has the potential in replacing steel and concrete and as option for a more sustainable building material. The mean values also charted more than 3.0 which show high confidence in them in using EWP as building material. Most of the senior practitioners are aware of the product and open towards the integration of EWP in their designs. It is hoped that EWP production can be further improved to suit various needs and requirements in building design.